Overview of Developments in the MRCC Program System - Mester, Dávid; Nagy, Péter R; Csóka, József; Gyevi-Nagy, László; Szabó, P Bernát; Horváth, Réka A; Petrov, Klára; Hégely, Bence; Ladóczki, Bence; Samu, Gyula; Lőrincz, Balázs D; Kállay, Mihály (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2025)
mrcc is a versatile suite of quantum chemistry programs designed for accurate and density functional theory (DFT) calculations. This contribution outlines the general features and recent developments of the package. The most popular features include the open-ended coupled-cluster (CC) code, state-of-the-art CC singles and doubles with perturbative triples [CCSD(T)], second-order algebraic-diagrammatic construction, and combined wave function theory-DFT approaches. Cost-reduction techniques are implemented, such as natural orbital (NO), local NO (LNO), and natural auxiliary function approximations, which significantly decrease the computational demands of these methods. This paper also details the method developments made over the past five years, including efficient schemes to approach the complete basis set limit for CCSD(T) and the extension of our LNO-CCSD(T) method to open-shell systems. Additionally, we discuss the new approximations introduced to accelerate the self-consistent field procedure and the cost-reduction techniques elaborated for analytic gradient calculations at various levels. Furthermore, embedding techniques and novel range-separated double-hybrid functionals are presented for excited-state calculations, while the extension of the theories established to describe core excitations and ionized states is also discussed. For academic purposes, the program and its source code are available free of charge, and its commercial use is also facilitated.